A Sociopragmatic Analysis of Complaining Acts in the 2005 British Film Pride and Prejudice - Ayat Muhammad Jabbar; Tawfeeq Majeed Ahmed (مجلة الباحث, 2025)
This study conducts a sociopragmatic analysis of complaining acts as represented in the 2005 British film Pride and Prejudice. It attempts to answer the following questions: 1. What are the most frequently employed speech acts within complaint sequences, and what interactional functions do these acts serve? 2. How do characters construct and use different complaint strategies and types, and how frequently do they occur? To examine the data, the researcher applies Searle's (1976) classification of speech acts and Trosborg's (1994) taxonomy of complaint strategies using a descriptive qualitative approach supported by quantitative elements, i.e. percentages and frequencies. Based on the findings, the study indicates that Expressive speech acts are predominantly used in complaints (60%), allowing characters to convey dissatisfaction within social constraints. Among Trosborg's strategies, "Annoyance or Disapproval" (37.03%) and "Direct Accusation" (25.94%) are most prevalent, while "Hints," "Consequences," and "Indirect Accusation" are notably absent.